Trioxane or methylal production method
By employing a styrene resin with a specific surface area and head space ratio, the method addresses the degradation issues in cation exchange resins, ensuring sustained reaction activity and mechanical integrity for trioxane and methylal production.
Patent Information
- Application Number
- JP2023102792
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-22
- Publication Date
- 2025-01-09
AI Technical Summary
Existing methods for producing trioxane and methylal using cation exchange resins face issues such as a decrease in ion exchange capacity and mechanical strength over time, leading to reduced reaction activity and equipment deterioration.
The method involves using a styrene resin with a specific surface area of 10 to 100 m²/g and a head space ratio of 10 to 80% in a catalyst-filled tank, along with a continuous reaction format, to produce trioxane or methylal, utilizing electron-withdrawing groups and controlling the resin's structure through precipitant and crosslinking agent amounts.
This approach effectively suppresses the decrease in reaction activity and mechanical strength of the styrene resin even after long-term use, maintaining efficient production of trioxane or methylal.
Smart Images

Figure 2025002548000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a process for the preparation of trioxane or methylal. [Background technology]
[0002] Trioxane is a cyclic trimer of formaldehyde and is mainly used as a raw material for the production of polyoxymethylene. Methylal is obtained by reacting formaldehyde with methanol, and high-concentration formaldehyde can be obtained by oxidizing methylal.
[0003] Both the methods for producing trioxane and methylal use formaldehyde as a raw material and an acid catalyst (e.g., sulfuric acid, benzenesulfonic acid, toluenesulfonic acid, silica alumina, zeolite, cation exchange resin, etc.), and have common problems.
[0004] The general industrial method for producing trioxane is to use sulfuric acid, but this method has problems such as corrosion of the equipment, generation of a large amount of by-products, and generation of paraformaldehyde.
[0005] As a method for solving these problems, a method using a styrene-based resin, particularly a cation exchange resin, has been proposed. As a method for producing trioxane from formaldehyde using a cation exchange resin, Patent Document 1 discloses a method using a cation exchange resin having an -SO3H group as an exchange group.
[0006] Furthermore, Patent Document 2 discloses a method using a macroreticular cation exchange resin as a method with good selectivity for trioxane. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Special Publication No. 40-12794 [Patent Document 2] Special Publication No. 64-11025 Summary of the Invention [Problem to be solved by the invention]
[0008] When producing trioxane using a cation exchange resin, in order to produce trioxane efficiently, it is preferable to bring an aqueous formaldehyde solution into contact with the cation exchange resin.
[0009] However, when the reaction is continued while the aqueous formaldehyde solution is in contact with the cation exchange resin, there is a problem that the sulfonic acid groups are eliminated from the cation exchange resin, decreasing the ion exchange capacity and the activity for synthesizing trioxane.
[0010] Furthermore, if the reaction is continued for a long period of time, the cation exchange resin deteriorates, reducing its mechanical strength and leading to crushing, which may result in contamination of the process system.
[0011] Therefore, an object of the present invention is to provide a method for producing trioxane or methylal, which suppresses a decrease in the target reaction activity even when used for a long period of time and a decrease in the mechanical strength of a styrene-based resin. [Means for solving the problem]
[0012] As a result of extensive investigations, the present inventors have found that the above-mentioned problems can be solved by setting the specific surface area of the styrene-based resin within an optimal range, and have thus completed the present invention.
[0013] That is, the present invention is as follows. [1] A method for producing trioxane or methylal, comprising the steps of: The method includes a step of reacting formaldehyde in the presence of a styrene-based resin having an electron-withdrawing group to produce trioxane or methylal, The specific surface area of the styrene-based resin measured by nitrogen adsorption is 10 to 100 m 2 / g of trioxane or methylal. [2] The method for producing trioxane or methylal according to [1], wherein the styrene-based resin is a cation exchange resin. [3] The method for producing trioxane or methylal according to [1] or [2], wherein the styrene-based resin is a compound containing structural units represented by the following formulas (I) and (II): [ka] In formulas (I) and (II), R 1 , R 2 and R 3 each independently represents a hydrogen atom, an alkyl group, an aryl group, or a halogen atom; X is an electron-withdrawing group, and a plurality of X's may be different from each other; Y is an alkylene group, an arylene group, or a single bond; Each a is independently an integer of 1 to 5; Each b is independently an integer of 1 to 4. [4] A catalyst-filled vessel is provided. The method for producing trioxane or methylal according to any one of [1] to [3], wherein the upper void ratio is a ratio of a space in the catalyst-filled vessel that is not filled with the styrene-based resin after the catalyst-filled vessel is filled with the styrene-based resin to a total volume of the catalyst-filled vessel that can be filled with the styrene-based resin, and the upper void ratio is 10 to 80%. [5] The method for producing trioxane or methylal according to any one of [1] to [4], wherein the reaction of formaldehyde in the step is a continuous reaction. [6] The method for producing trioxane or methylal according to [4] or [4], wherein a residence time of formaldehyde in the catalyst-packed tank is 0.01 to 50 minutes. Effect of the Invention
[0014] According to the present invention, there can be provided a method for producing trioxane or methylal, which suppresses a decrease in the target reaction activity even when used for a long period of time and a decrease in the mechanical strength of the styrene-based resin. [Brief description of the drawings]
[0015] [Figure 1] FIG. 1 is a flow diagram that illustrates an example of a process for producing trioxane according to the present embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] Hereinafter, an embodiment of the present invention (hereinafter, simply referred to as "the present embodiment") will be described in detail. Note that the present invention is not limited to the following description, and can be practiced in various modifications within the scope of the gist of the present invention.
[0017] The specific surface area of the styrene-based resin in this embodiment is a value measured by a nitrogen adsorption method under the measurement conditions described in the examples described later.
[0018] In this embodiment, the ratio of the space in the catalyst-filled vessel that is not filled with the styrene-based resin after it has been filled with the styrene-based resin to the total volume of the catalyst-filled vessel that can be filled with the styrene-based resin is referred to as the upper void ratio.
[0019] In this embodiment, the method includes a step of producing trioxane or methylal by reacting formaldehyde in the presence of a styrene-based resin having an electron-withdrawing group, and the specific surface area of the styrene-based resin is 10 to 100 m. 2 / g.
[0020] In a preferred embodiment, the styrene-based resin having an electron-withdrawing group is, for example, a compound containing structural units represented by the following formulas (I) and (II). [ka] In formula (I), R 1 , R 2 and R3 each independently represents a hydrogen atom, an alkyl group, an aryl group, or a halogen atom; X is an electron-withdrawing group, and a plurality of X's may be different from each other; Each a is independently an integer of 1 to 5. In formula (II), R 1 , R 2 and R 3 each independently represents a hydrogen atom, an alkyl group, an aryl group, or a halogen atom; X is an electron-withdrawing group, and a plurality of X's may be different from each other; Y is an alkylene group, an arylene group, or a single bond; Each a is independently an integer of 1 to 5. Each b is independently an integer of 1 to 4.
[0021] R in formula (I) and (I) 1 , R 2 and R 3 Examples of the alkyl group include linear, branched, and cyclic alkyl groups. Examples of linear alkyl groups include methyl, ethyl, propyl, and butyl groups. Examples of branched alkyl groups include isopropyl, isobutyl, and tert-butyl groups. Examples of cyclic alkyl groups include cyclopropyl, cyclobutyl, cyclopentyl, and cyclohexyl groups.
[0022] R in formulas (I) and (II) 1 , R 2 and R 3 Examples of the aryl group include a phenyl group, a 1-naphthyl group, a 2-naphthyl group, an anthryl group, and a phenanthryl group.
[0023] R in formulas (I) and (II) 1 , R 2 and R 3 Examples of the halogen atom include a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom.
[0024] R in formulas (I) and (II) 1 , R 2 and R 3 The alkyl group and the aryl group may or may not have a substituent. Examples of the substituent include R 1 Examples of the alkyl group include the alkyl group and halogen atoms exemplified above.
[0025] In a preferred embodiment, R 1 , R 2 , and R 3 is a hydrogen atom.
[0026] Examples of the electron-withdrawing group X in formulae (I) and (II) include a sulfonic acid group, a carboxylic acid group, a nitro group, a cyano group, a phosphoric acid group, a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom.
[0027] Examples of the alkylene group include linear, branched, and cyclic alkylene groups such as methylene and ethylene groups. The alkylene group may or may not have a substituent. Examples of the substituent include R 1 Examples of the alkyl group include the alkyl group and halogen atoms exemplified above.
[0028] The arylene group of Y in formula (II) may be, for example, a phenylene group. The arylene group may or may not have a substituent. Examples of the substituent include R 1 Examples of the alkyl group include the alkyl group and halogen atoms exemplified above.
[0029] When Y in formula (II) is a single bond, the aromatic ring and the carbon of the main chain are directly bonded.
[0030] In a preferred embodiment, Y is a single bond.
[0031] The terminals of the compound containing the structural units represented by formulae (I) and (II) are not particularly limited, and may have the above-mentioned substituents or may have a substituent derived from the polymerization initiator.
[0032] The specific surface area of the styrene-based resin used in this embodiment, as measured by a nitrogen adsorption method, is 10 to 100 m 2 The upper limit of the specific surface area of styrene resins is 100 m from the viewpoint of the rate of change in mechanical strength. 2 / g, preferably 80m 2 / g, more preferably 60m 2 On the other hand, the lower limit of the preferred range is 20 m / g from the viewpoint of the reactivity change rate. 2 / g, more preferably 30m 2 / g.
[0033] Methods for controlling the specific surface area include, for example, (1) a method of adjusting the amount of a precipitating agent added in polymerization, and (2) a method of adjusting the amount of a crosslinking agent added. The above methods (1) and (2) may be used alone or in combination.
[0034] The precipitant has the function of forming a porous structure of the styrene-based resin. In addition, the larger the amount of the precipitant, the larger the specific surface area of the styrene-based resin tends to be. Examples of the precipitant include 2-butanol, 2-methyl 2-butanol, and heptane. A preferred precipitant is 2-butanol. The amount of the precipitant added is, for example, 0% by weight or more, 40% by weight or more, 80% by weight or more, 120% by weight or more, or 160% by weight or more, and 200% by weight or less, 160% by weight or less, 120% by weight or less, 80% by weight or less, or 40% by weight or less, based on the total monomer weight in the polymerization.
[0035] The crosslinking agent has the function of forming a three-dimensional network structure of the styrene resin. Examples of the crosslinking agent include divinylbenzene, divinylbiphenyl, and trivinylbenzene. A preferred crosslinking agent is divinylbenzene. The amount of the crosslinking agent added is, for example, 5% by weight or more, 10% by weight or more, 15% by weight or more, 30% by weight or more, or 40% by weight or more, and 50% by weight or less, 40% by weight or less, 30% by weight or less, 15% by weight or less, or 10% by weight or less, based on the total monomer weight in the polymerization.
[0036] Method for producing trioxane Fig. 1 is a flow diagram showing a schematic example of a process for producing trioxane according to the present embodiment. In the example shown in Fig. 1, a raw material (aqueous formaldehyde solution) is supplied from a raw material supply line 1 to the bottom of a distillation column 2. Then, the liquid inside the distillation column 2 is circulated through a catalyst-packed tank 3 and a reboiler 4 at a predetermined temperature to synthesize trioxane. Then, trioxane, water, formaldehyde and by-products are distilled from a distillation line 5 at the top of the column. Next, the distillate containing trioxane is contacted with an organic solvent to extract trioxane into the organic solvent phase, and the extract is further purified to obtain high-purity trioxane.
[0037] Since a styrene-based resin having a large specific surface area swells more easily, a higher upper space ratio is preferable from the viewpoint of operation management. From the viewpoint of the reactivity change rate, the upper limit of the preferred range of the upper space ratio of the catalyst-packed vessel is 80%, more preferably 75%, and even more preferably 70%. On the other hand, the lower limit of the preferred range is 10%, more preferably 15%, and even more preferably 20%. By setting the upper space ratio to 10 to 80%, the decrease in the reactivity change rate is further suppressed.
[0038] In the preferred method for producing trioxane or methylal in this embodiment, the reaction type is not particularly limited, and examples thereof include a batch type, a semi-batch type, and a continuous type. As the reaction type, a continuous type is preferred.
[0039] The residence time of the raw material liquid containing formaldehyde in the catalyst-filled tank is not particularly limited and can be, for example, 0.01 to 60 minutes. In a preferred embodiment, the residence time is 50 minutes or less, 40 minutes or less, 30 minutes or less, 20 minutes or less, or 10 minutes or less. In another preferred embodiment, the residence time is 0.01 minutes or more, 0.1 minutes or more, or 1 minute or more.
[0040] In this embodiment, an aqueous formaldehyde solution may be used as a raw material. The concentration of formaldehyde in the aqueous formaldehyde solution is not particularly limited and is, for example, 30 to 80% by weight, and preferably 60 to 75% by weight.
[0041] An example of an industrial implementation of this embodiment is as follows.
[0042] Method for producing methylal In the production of methylal, an aqueous formaldehyde solution and methanol are supplied as raw materials in the production of trioxane, and methylal is synthesized by a process similar to that shown in FIG. 1, and the produced methylal is distilled from the top of the distillation column 2.
[0043] Although the embodiment of the present invention has been described above, the present invention is not limited to the above embodiment. The present invention can be modified in various ways without departing from the gist of the present invention. EXAMPLES
[0044] The present invention will be described in detail below with reference to specific examples and comparative examples, but the present invention is not limited to the following examples. The terms and measurement methods for properties in the examples and comparative examples are as follows.
[0045] (1) Specific surface area (m 2 / g) The specific surface area of the styrene-based resin was measured by a nitrogen adsorption method under the following conditions. (Pretreatment) The samples were frozen at -10°C for 24 hours, and then vacuum dried at 25°C and 0.01 MPa until the weight did not change, after which the measurements were performed. (Measurement conditions) Equipment: Micro Meritics 3-Flex Adsorption gas: N2 gas Measurement temperature: -195℃ (under liquid nitrogen) Sample size: 0.5g Calculation method: BET method
[0046] (Gas chromatography measurement conditions) Equipment: Shimadzu GC2014S Detector: Thermal conductivity detector (TCD) Filler: Porapack T (50 / 80 mesh) manufactured by Japan Waters Inlet temperature: 230℃ Column temperature: 125-180℃ Detection temperature: 230℃ (After holding for 8 minutes, increase the temperature to 180°C at 20°C / min and hold at 180°C for 15 minutes) Carrier gas: Hydrogen
[0047] Long-term testing The styrene resin obtained in the manufacturing example was placed in a graduated cylinder, pure water was added until the styrene resin was completely immersed, and the top surface of the styrene resin was leveled to the 125 mL position. The water in the styrene resin was thoroughly removed, and the resin was transferred to a pressure-resistant container with a polytetrafluoroethylene (PTFE) inner cylinder (PTFE inner cylinder sealed heating reactor, model number: YHR-250N, volume 250 mL). 50 mL of 67 wt% formaldehyde aqueous solution heated to 100°C was placed in the pressure-resistant container, stirred with a spatula, and the supernatant liquid was removed. This operation was repeated four times. Next, the formaldehyde aqueous solution was added up to the top surface of the styrene resin, and the container was sealed. The container was placed in an oven (manufactured by Espec, model number: LCV-233) that had been preheated to 110°C. The time when the container was placed in the oven was used as the starting time, and 24 hours later was considered to be one day. After 150 days had passed, the container was removed from the oven and cooled to room temperature. Next, the styrene-based resin was taken out of the container and washed with pure water.
[0048] (2) Change in reactivity before and after long-term testing (%) 20 mL of styrene resin was measured before and after the long-term test and filled into a glass tube. 67 wt% formaldehyde aqueous solution heated to 100°C was continuously supplied at 200 g / hr to a glass tube heated to 100°C. 120 mL or more of the formaldehyde aqueous solution was passed through. 1 g of the reaction solution after passing through was sampled, and 10 g of heated pure water was added to make a homogeneous solution. Using each solution before and after the long-term test, the target product, trioxane or methylal concentration (wt%) was measured to evaluate the reactivity change rate. Gas chromatography was used under the following conditions. It was determined that if the reactivity change rate was 70% or more, the target reaction activity could be suppressed and production could be performed even with long-term use. The rate of change in reactivity (%) before and after the long-term test was calculated using the following formula. Reactivity change rate (%) = "Concentration (wt%) of the target product in the presence of styrene-based resin after the test / Concentration (wt%) of the target product in the presence of styrene-based resin before the test" x 100
[0049] (3) Change in mechanical strength before and after long-term testing (%) The mechanical strength of the styrene-based resin before and after the long-term test was measured using a load displacement measuring device under the following conditions. (Load displacement measuring instrument measurement conditions) Equipment: Force gauge (ZTA-5N) Test speed: 0.5mm / min A vacuum-dried granular sample is placed on the measurement stage, and the maximum load value (N) at which it is crushed when compressed from above with a flat surface is measured. Approximately 50 grains are measured and the average value is calculated. The rate of change in mechanical strength was calculated from the following formula. It was determined that if the rate of change in mechanical strength was 70% or more, the styrene-based resin could be produced while suppressing the decrease in mechanical strength even after long-term use. Mechanical strength change rate (%) = "(Maximum load value after long-term test) / (Maximum load value before long-term test)" x 100
[0050] Production Example 1: Production of styrene-based resin 1 Mixture 1 was prepared, consisting of 360 g of styrene, 72 g of divinylbenzene, 3.8 g of benzoyl peroxide, and 500 g of 2-butanol. Then, an aqueous solution was prepared by dissolving 27 g of sodium chloride and 3 g of ammonium salt of styrene-maleic anhydride copolymer in 722 g of water. Mixture 1 was then added to the aqueous solution to obtain Mixture 2. When Mixture 2 was stirred, the organic phase was dispersed in the form of fine droplets. Mixture 2 was heated to 86-92°C for 6 hours to carry out the polymerization reaction. Next, steam was passed through the reaction mixture to remove the azeotrope of 2-butanol and water. Next, the formed beads were filtered, washed with water, and dried at 125°C for 5 hours. 540 g of white opaque polymer in the form of spherical or elliptical particles was obtained. 70 g of the obtained polymer and 800 g of sulfuric acid were heated to 118-122°C for 7 hours with stirring. Next, the mixture was cooled to about 35°C and diluted with water. The solid product was filtered, washed with water to remove water-soluble products, and filtered to obtain 273 g of a sulfonated product, a styrene-based resin (cation exchange resin).
[0051] Production Example 2: Production of styrene-based resin 2 The same treatment as in Production Example 1 was carried out except that the amount of divinylbenzene was changed to 65 g, the amount of 2-butanol was changed to 400 g, and 543 g of polymer was obtained, thereby obtaining 270 g of a styrene-based resin (cation exchange resin) as a sulfonation product.
[0052] Example 3: Manufacture of styrene resin 3 The same treatment as in Production Example 1 was carried out except that the amount of divinylbenzene was changed to 65 g, the amount of 2-butanol was changed to 300 g, and 543 g of polymer was obtained, thereby obtaining 275 g of a styrene-based resin (cation exchange resin) as a sulfonation product.
[0053] Production Example 4: Production of styrene-based resin 4 The same treatment as in Production Example 1 was performed except that the amount of divinylbenzene was changed to 65 g, the amount of 2-butanol was changed to 700 g, and 543 g of polymer was obtained, thereby obtaining 273 g of a styrene-based resin (cation exchange resin) as a sulfonation product.
[0054] Production Example 5: Production of styrene-based resin 5 The same treatment as in Production Example 1 was carried out except that the amount of divinylbenzene was changed to 65 g, the amount of 2-butanol was changed to 350 g, and 543 g of polymer was obtained, thereby obtaining 275 g of a styrene-based resin (cation exchange resin) as a sulfonation product.
[0055] Production Example 6: Production of styrene-based resin 6 The same treatment as in Production Example 1 was performed except that the amount of divinylbenzene was changed to 65 g, the amount of 2-butanol was changed to 600 g, and 543 g of polymer was obtained, thereby obtaining 273 g of a styrene-based resin (cation exchange resin) as a sulfonation product.
[0056] Production Example 7: Production of styrene-based resin 7 The same treatment as in Production Example 1 was carried out except that the amount of divinylbenzene was changed to 65 g, the amount of 2-butanol was changed to 200 g, and 543 g of polymer was obtained, thereby obtaining 271 g of a styrene-based resin (cation exchange resin) as a sulfonation product.
[0057] Production Example 8: Production of styrene-based resin 8 The same treatment as in Production Example 1 was carried out except that the amount of divinylbenzene was changed to 65 g, the amount of 2-butanol was changed to 800 g, and 543 g of polymer was obtained, thereby obtaining 274 g of a styrene-based resin (cation exchange resin) as a sulfonation product.
[0058] The styrene-based resins of Production Examples 1 to 8 are each represented by the formula (I) and the formula (II), 1 , R 2 and R 3was a hydrogen atom, X was -SO3H, Y was a single bond, a was an integer of 1 to 5, and b was an integer of 1 to 4.
[0059] Example 1 The styrene resin 1 obtained in Production Example 1 was placed in a graduated cylinder, pure water was added until the styrene resin was completely immersed, and the top surface of the styrene resin was leveled to the 125 mL position. The water in the styrene resin was thoroughly removed, and the styrene resin was transferred to a PTFE inner cylinder pressure-resistant vessel (PTFE inner cylinder sealed heating reactor, model number: YHR-250N, volume 250 mL) which was a catalyst-filled vessel. 50 mL of 67 wt% formaldehyde aqueous solution heated to 100°C was placed in the vessel, stirred with a spatula, and the supernatant liquid was removed. After repeating this operation four times, the formaldehyde aqueous solution was added up to the top surface of the styrene resin, the vessel was sealed, and placed in an oven (manufactured by Espec Corporation, model number: LCV-233) previously heated to 110°C. After 150 days had passed (the time when it was placed in the oven was taken as the start time, and 24 hours later was taken as one day), the vessel was removed from the oven and cooled to room temperature, and the styrene resin was removed from the vessel and washed with pure water. The mechanical strength of the styrene-based resin was measured using a load-displacement measuring device, and the percentage change in mechanical strength before and after the long-term test was calculated as described above.
[0060] 20 mL of styrene resin was measured before and after the long-term test and filled into a glass tube. A 67 wt% aqueous formaldehyde solution heated to 100°C was continuously fed at 200 g / hr into the glass tube heated to 100°C. After 120 mL or more of the aqueous formaldehyde solution was passed through, 1 g of the reaction liquid was sampled and 10 g of heated pure water was added to make a homogenous solution, and the concentration (wt%) of the generated trioxane was measured using gas chromatography.
[0061] Example 2 Each evaluation was carried out in the same manner as in Example 1, except that the styrene-based resin 2 was used instead of the styrene-based resin 1.
[0062] Example 3 Each evaluation was carried out in the same manner as in Example 1, except that styrene-based resin 3 was used instead of styrene-based resin 1, and the amount of styrene-based resin charged for the long-term test was changed to 75 mL.
[0063] Example 4 Each evaluation was carried out in the same manner as in Example 1, except that the styrene-based resin 1 was replaced with the styrene-based resin 4, and the amount of the styrene-based resin charged in the long-term test was changed to 200 mL.
[0064] Example 5 Each evaluation was carried out in the same manner as in Example 1, except that the styrene-based resin 5 was used instead of the styrene-based resin 1, and the amount of the styrene-based resin charged in the long-term test was changed to 175 mL.
[0065] Example 6 Each evaluation was carried out in the same manner as in Example 1, except that styrene-based resin 6 was used instead of styrene-based resin 1, and the amount of styrene-based resin charged for the long-term test was changed to 100 mL.
[0066] Example 7 150 mL of the styrene resin 1 synthesized in Production Example 1 was measured with a graduated cylinder and filled into a catalyst-filled tank with a volume of 300 mL. A 67% by weight aqueous formaldehyde solution heated to 100°C was supplied to the bottom of an Oldershaw distillation tower (15 stages), and the catalyst-filled tank was installed in the circulation line (bottom to catalyst-filled tank), and the bottom liquid was circulated at a circulation liquid rate of 1500 g / hr. The bottom was heated with a heater, distilled without reflux, and the distillate was extracted at 150 g / hr to synthesize trioxane. The amount of the formaldehyde aqueous solution supplied to the bottom was controlled so that the level of the bottom liquid was constant. After this state was continued for 1 hour, 1 g of the reaction liquid after passing through the catalyst-filled tank was sampled, and 10 g of heated pure water was added to make a homogeneous solution, and the concentration (wt%) of the produced trioxane was measured using gas chromatography.
[0067] After the test was conducted for 150 consecutive days, 1 g of the reaction liquid after passing through the catalyst-filled tank was sampled, and 10 g of heated pure water was added to prepare a homogeneous solution. The concentration (wt%) of the produced trioxane was measured using gas chromatography.
[0068] After 150 days of continuous testing, the styrene resin was removed from the catalyst tank and washed with pure water. The mechanical strength of the styrene resin was measured using a load displacement measuring device, and the percentage change in mechanical strength before and after the long-term test was calculated.
[0069] 20 mL of each styrene resin before and after the long-term test was measured with a measuring cylinder and filled into a glass tube. A 67 wt% aqueous formaldehyde solution heated to 100°C was continuously fed at 200 g / hr into the glass tube heated to 100°C. After 120 mL or more of the aqueous formaldehyde solution was passed through, 1 g of the reaction liquid after passing through was sampled, and 10 g of heated pure water was added to make a homogenous solution, and the concentration (wt%) of the generated trioxane was measured using gas chromatography.
[0070] Example 8 20 mL of the styrene resin 1 synthesized in Production Example 1 was measured with a graduated cylinder and transferred to a pressure-resistant container with a PTFE inner cylinder (PTFE inner cylinder sealed heating reactor, model number: YHR-250N, volume 250 mL). 50 mL of a mixture of 30% by weight formaldehyde aqueous solution and methanol (molar ratio of formaldehyde simple substance to methanol is formaldehyde:methanol=1:2) heated to 70°C was placed in the container, stirred with a spatula, and the supernatant liquid was removed. After repeating this operation four times, the mixture was added up to the position of the top surface of the styrene resin, the container was sealed, and placed in an oven (manufactured by Espec Corporation, model number: LCV-233) previously heated to 110°C. After 150 days (the time when it was placed in the oven is taken as the start time, and 24 hours later is taken as one day), the container was removed from the oven and cooled to room temperature, and the styrene resin was removed from the container and washed with pure water. The mechanical strength of the styrene-based resin was measured using a load-displacement measuring device, and the percentage change in mechanical strength before and after the long-term test was calculated as described above.
[0071] As described above, 20 mL of each styrene resin before and after the long-term test was measured with a measuring cylinder and filled into a glass tube. A mixture of 30% by weight aqueous formaldehyde solution and methanol (molar ratio 1:2) heated to 70°C was continuously fed at 200 g / hr into the glass tube heated to 70°C. After passing 120 mL or more of the mixture, 1 g of the reaction liquid after passing was sampled, and 10 g of heated pure water was added to make a homogenous solution, and the concentration (wt%) of the generated methylal was measured using gas chromatography.
[0072] Comparative Example 1 Each evaluation was carried out in the same manner as in Example 1, except that styrene-based resin 7 was used instead of styrene-based resin 1.
[0073] Comparative Example 2 Except for using styrene-based resin 8 instead of styrene-based resin 1, the same procedures as in Example 1 were carried out to carry out the various evaluations.
[0074] The evaluation results are shown in Table 1. [Table 1] In the table, the target product "T" stands for trioxane, and "M" stands for methylal.
[0075] In Examples 1 to 8, the rate of change in mechanical strength and the rate of change in reactivity of the styrene-based resin before and after the test were satisfactory.
[0076] On the other hand, in Comparative Example 1, the specific surface area of the styrene-based resin 7 was outside the range of the present invention, and therefore the reactivity change rate was not satisfactory.
[0077] In Comparative Example 2, the specific surface area of the styrene-based resin 8 was outside the range of the present invention, and therefore the rate of change in mechanical strength of the styrene-based resin was not satisfactory. [Industrial Applicability]
[0078] INDUSTRIAL APPLICABILITY The present invention has industrial applicability as a method for producing trioxane or methylal, which suppresses a decrease in the target reaction activity and a decrease in the mechanical strength of a styrene-based resin even after long-term use. [Explanation of symbols]
[0079] 1: Raw material supply line 2: Distillation tower 3:Catalyst filling tank 4: Reboiler 5: Distillation line
Claims
1. A method for producing trioxane or methylal, comprising the steps of: The method includes a step of reacting formaldehyde in the presence of a styrene-based resin having an electron-withdrawing group to produce trioxane or methylal, The specific surface area of the styrene-based resin as measured by a nitrogen adsorption method is 10 to 100 m 2 / g of trioxane or methylal.
2. The method for producing trioxane or methylal according to claim 1, wherein the styrene-based resin is a cation exchange resin.
3. The method for producing trioxane or methylal according to claim 1, wherein the styrene-based resin is a compound containing structural units represented by the following formulas (I) and (II): 【Chemistry 1】 (In formulas (I) and (II), R 1 , R 2 and R 3 each independently represents a hydrogen atom, an alkyl group, an aryl group, or a halogen atom; X is an electron-withdrawing group, and a plurality of X's may be different from each other; Y is an alkylene group, an arylene group, or a single bond; Each a is independently an integer from 1 to 5; Each b is independently an integer from 1 to 4.
4. A catalyst-filled vessel is provided.
2. The method for producing trioxane or methylal according to claim 1, wherein the upper void ratio is a ratio of a space in the catalyst-filled vessel that is not filled with the styrene-based resin after the catalyst-filled vessel is filled with the styrene-based resin to a total volume of the catalyst-filled vessel that can be filled with the styrene-based resin, and the upper void ratio is 10 to 80%.
5. 2. The method for producing trioxane or methylal according to claim 1, wherein the reaction of formaldehyde in the step is a continuous reaction.
6. 5. The method for producing trioxane or methylal according to claim 4, wherein the residence time of formaldehyde in the catalyst-packed tank is 0.01 to 50 minutes.
Citation Information
Patent Citations
JP1965012794B
Production of projecting part for cylindrical pipe
JP1989011025A